Effects of bed composition on turbidity flow dynamics in relation to flocculation - Wahab, Shaheen Akhtar; Chassagne, Claire; Helmons, Rudy L. J. (Frontiers in Marine Science, 2025)
This study investigated the impact of various types of bed composition on turbidity current propagation in relation to flocculation. A lock exchange setup was used, comprising a mixing section and an outflow compartment. The bed types investigated were a quartz bed, a quartz bed topped with (unflocculated) illite clay, and a quartz bed with flocculated illite. The findings confirmed that the presence of a bed influenced the turbidity current propagation. In particular, it was found that the front velocity was strongly reduced when the bed was composed of freshly made flocs compared to the case where the bed was made of quartz alone, which does not form flocs. While propagating, either illite clay or flocs were picked up and aggregated into larger flocs. These larger flocs were then deposited further downstream during propagation. Moreover, the front velocity was higher over a quartz bed when no flocculant was added to the outflow compartment water than when flocculant was present. This confirms that flocculation occurs in the water column during propagation.